The Relationship between English Learning Motivation and Junior High School Student’s Speaking Ability - Lailisabila, Madina; Aminullah, Aminullah (Journal of Language Intelligence and Culture, 2022)
This study aims to determine whether there is a correlation between English learning motivation and students speaking ability. The research used a quantitative method in correlational research design and statistical tests of IBM SPSS 20 with the Spearman-rank Correlation test formula. After testing both variables, the data shows no relationship between English learning motivation and students speaking ability. The inferential statistical analysis results show that the result of the Spearman-rank Correlation test is valued as much as Sig = 0.224 < 0.05 (there is no correlation) with a correlation coefficient of 0.167. Eventually, the correlation test results between learning motivation and students' speaking ability show that students' speaking ability is not thoroughly influenced by motivation in learning English.